Can students learn what the textbook says? A Cognitive outlook into an Indonesian EFL textbook - Suherman, Rudi; Latifah, Nur Fitri (Jurnal Cakrawala Pendidikan, 2025)
Findings from Second Language Acquisition (SLA) research, which offer critical insights into how learners acquire and process language, are often overlooked in the development of curricula and textbooks for early English Language Teaching (ELT). This raises questions about the feasibility of the learning objectives promoted in these materials. To address this gap, this study analyzes a junior high school EFL textbook within the framework of Processability Theory (PT) to examine whether the sequencing of grammatical structures aligns with the teachability hierarchy predicted by PT. The analysis focuses on the grading of grammatical structures and compares their distribution with the stages of acquisition prescribed by PT. The findings reveal only a partial alignment with the PT hierarchy, highlighting a disconnect between textbook design and learners' developmental stages. This misalignment is largely due to the theme-based approach being adopted by the textbook and therefore highlights the need for textbook writers, curriculum developer and English teacher to better integrate SLA research into developing textbooks, particularly in the context of the Kurikulum Merdeka, which emphasizes learner-centered education and learners’ cognitive liberation.